From gene to brain to behavior: schizophrenia‐associated variation in AMBRA1 alters impulsivity‐related traits. Issue 6 (2nd April 2013) - Heinrich, Angela; Nees, Frauke; Lourdusamy, Anbarasu; Tzschoppe, Jelka; Meier, Sandra; Vollstädt‐Klein, Sabine; Fauth‐Bühler, Mira; Steiner, Sabina; Bach, Christiane; Poustka, Luise; Banaschewski, Tobias; Barker, Gareth J.; et al.
Abstract Recently, genome‐wide association between schizophrenia and an intronic variant in AMBRA1 (rs11819869) was reported. Additionally, in a reverse genetic approach in adult healthy subjects, risk allele carriers showed a higher medial prefrontal cortex blood oxygen level‐dependent (BOLD) response during a flanker task examining motor inhibition as an aspect of impulsivity. To test whether this finding can be expanded to further aspects of impulsivity, we analysed the effects of the rs11819869 genotype on impulsivity‐related traits on a behavioral, temperament and neural level in a large sample of healthy adolescents. We consider this reverse genetic approach specifically suited for use in a healthy adolescent sample, as these individuals comprise those who will eventually develop mental disorders in which impulsivity is implicated. Healthy adolescents from the IMAGEN study were included in the neuropsychological analysis (n = 848) and a functional magnetic resonance imaging (fMRI) task (n = 512). Various aspects of impulsivity were assessed using the Temperament and Character Inventory‐Revised, the Substance Use Risk Profile Scale, the Cambridge Cognition Neuropsychological Test Automated Battery, and the Stop Signal Task (SST) in the fMRI paradigm. On a behavioral level, increased delay aversion was observed in risk allele carriers. Furthermore, risk allele carriers showed a higher BOLD response in an orbito‐frontal target region during the SST, which declined to trend status after Family Wise Error correction. Our findings support the hypothesis that the schizophrenia‐related risk variant of rs11819869 is involved in various aspects of impulsivity, and that this involvement occurs on a behavioral as well as an imaging genetics level.